2009
DOI: 10.1016/j.peptides.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an iberiotoxin derivative by chemical ligation: A method for improved yields of cysteine-rich scorpion toxin peptides

Abstract: Automated and manual solid phase peptide synthesis techniques were combined with chemical ligation to produce a 37-residue peptide toxin derivative of iberiotoxin which contained: (i) substitution of Val 16 to Ala, to facilitate kinetic feasibility of native chemical ligation, and; (ii) substitution of Asp 19 to orthogonally protected Cys-4-MeOBzl for chemical conjugate derivatization following peptide folding and oxidation. This peptide ligation approach increased synthetic yields approximately 12-fold compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previous studies of K + secretion in colon and renal epithelia have identified K Ca 1.1 (BK) channels as a predominant Ca 2+ ‐activated conductive pathway mediating K + efflux across the apical membrane (Sausbier et al 2006; Palmer & Frindt, 2007; Heitzmann & Warth, 2008; Sorensen et al 2010). To determine whether K Ca 1.1 channels were responsible for the I sc response evoked by UTP/ATP‐γ‐S in HME cells, the effects of two well‐characterized toxins (iberiotoxin and CTX) known to block BK channels were tested (Castle et al 1989; Kaczorowski et al 1996; Sorensen et al 2008; Bingham et al 2009). The results showed that iberiotoxin had no significant effect on the decrease in I sc , whereas CTX inhibited more than 90% of the P2Y receptor‐activated current.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of K + secretion in colon and renal epithelia have identified K Ca 1.1 (BK) channels as a predominant Ca 2+ ‐activated conductive pathway mediating K + efflux across the apical membrane (Sausbier et al 2006; Palmer & Frindt, 2007; Heitzmann & Warth, 2008; Sorensen et al 2010). To determine whether K Ca 1.1 channels were responsible for the I sc response evoked by UTP/ATP‐γ‐S in HME cells, the effects of two well‐characterized toxins (iberiotoxin and CTX) known to block BK channels were tested (Castle et al 1989; Kaczorowski et al 1996; Sorensen et al 2008; Bingham et al 2009). The results showed that iberiotoxin had no significant effect on the decrease in I sc , whereas CTX inhibited more than 90% of the P2Y receptor‐activated current.…”
Section: Discussionmentioning
confidence: 99%
“…Upon peptidyl‐resin reduction, the resin was flow‐washed with DMF (1 min, ×2) and coupled with Boc‐Cys(4‐MeOBzl) (40 min), as described above. The resulting pre‐loaded Boc‐Cys(4‐MeOBzl) thioester linker resin (Boc‐Cys(4‐MeOBzl)‐MPAL resin) was then used in the production of N‐ terminal peptide fragments for NCL at ∼0.5 mMole scale …”
Section: Methodsmentioning
confidence: 99%
“…A prominent example of this is ω-conotoxin MVIIA, which has been cited as a probe in over 2,000 scientific publications [16]. The potential for activity and structural investigation is being fostered by the ligation of visually traceable media such as biotin and fluorophores [41]. Many examples of the usefulness of conotoxins as probes exist in literature and include receptor subtypes in calcium channels, potassium channels, sodium channels, 5-HT 3 receptors, NMDA receptors and more [6,42].…”
Section: Conotoxins Used As Structural Toolsmentioning
confidence: 99%